2016
DOI: 10.1159/000443842
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Surgery for Locally Advanced Gallbladder Cancer with Obstructive Jaundice: Result of a Prospective Study

Abstract: Objective: The aim of this study was to clarify the clinical impact of our departmental policy for advanced gallbladder cancer (GBC) even with obstructive jaundice. Methods: Obstructive jaundice was defined as serum T-bil ≥2.0 mg/dl. Between 1998 and 2008, 112 patients with GBC were scheduled for surgical resection with curative intent. Thirty-six patients were converted to palliative surgery or exploration alone because of advanced disease. After excluding pathological T1 (UICC) patients (n = 11), the remaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 30 publications
(40 reference statements)
0
30
0
Order By: Relevance
“…Among the 168 studies that met the initial search criteria, eight studies were selected for the meta‐analysis. Figure illustrates a PRISMA diagram delineating the study selection process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the 168 studies that met the initial search criteria, eight studies were selected for the meta‐analysis. Figure illustrates a PRISMA diagram delineating the study selection process.…”
Section: Resultsmentioning
confidence: 99%
“…A funnel plot (Figure ) indicated no publication bias and an Egger’s test was nonsignificant ( P = 0.276). However, there were two outliers . Nasu et al reported comparable long‐term survival among patients who did and did not present with jaundice (5‐year survival of 31% vs 27% [ P = 0.742]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus preoperative jaundice should be considered a relative contraindication to radical resection for GBC [33]. However, recent reports have demonstrated declared that although preoperative jaundice indicates poor prognosis and high postoperative morbidity, it does not preclude radical resection, especially in highly selected patients (N0) [34,35], and aggressive surgery might improve long-term survival in advanced GBC patients with obstructive jaundice [36]. In this study, patients with obstructive jaundice who underwent curative resection had overall survival that were similar to those in patients without obstructive jaundice, and jaundice at diagnosis showed no prognostic impact once R0 was achieved.…”
Section: Discussionmentioning
confidence: 99%